THU0267 Gastrointestinal involvement in spondyloarthritis is not all ibd: increased risk of diverticulitis with longer disease duration in the asas-comospa cohort. (12th June 2018) - Derakhshan, M.H.; Goodson, N.; Packham, J.; Sengupta, R.; Molto, A.; Marzo-Ortega, H.; Siebert, S.
Abstract : Background: Inflammatory bowel disease (IBD) is an established extra-articular manifestation of Spondyloarthritis (SpA). The association of SpA with other gastrointestinal and hepatic comorbidities is less well known. Objectives: To examine the relationship between SpA disease duration and gastrointestinal comorbidities other than IBD. Methods: ASAS-COMOSPA is a large global cross-sectional study comprising 3984 patients with SpA. We evaluated the association between "SpA disease duration" (defined in 5 year blocks) and upper gastrointestinal ulcers, hepatitis B (HBV), hepatitis C (HCV) and diverticulitis. Binary logistic regression models were created, adjusted for age, sex, BMI, smoking, alcohol, NSAIDs, DMARDs, biologics, steroids and IBD history. Subgroup analysis was performed, stratified by peripheral and/or axial joint involvement. Results: The data of 3923 patients (64.9% male) were available for analysis, 5.3% of whom had a history of IBD. The self-reported prevalence of other gastrointestinal conditions was: upper gastrointestinal ulcers 10.7%; viral hepatitis 4.7% and diverticulitis 1.5%, with significant geographic variation. "SpA disease duration" was not associated with the occurrence of the upper gastrointestinal ulcers (OR=0.98, 95% CI: 0.92–1.05), HBV (OR=0.43, 95% CI: 0.28–0.67) or HCV (OR=0.27, 95% CI: 0.11–0.62). In contrast, the risk of diverticulitis was significantly increased by "SpA disease duration" (OR=1.14, 95% CI: 1.01–1.29); increased risk of 14% for every 5 years of disease duration) across the entire cohort, after adjustment for potential confounders, including age. Confounding variables showing significant association with diverticulitis were current age (OR=1.06, 95% CI: 1.04–1.08) and high alcohol (³3 units/day) intake (OR=3.84, 95% CI: 1.62–9.07) but not medication history (table 1). Subgroup analyses revealed stronger association of SpA disease duration with diverticulitis in those with axial (OR=1.24, 95% CI: 1.08–1.42) than those with peripheral (OR=1.12, 95% CI: 0.98–1.29) SpA disease. Conclusions: Patients with SpA have a number of gastrointestinal comorbidities, including increased risk of diverticulitis with increased SpA disease duration, highest in those with axial disease. The reasons for this association are unclear and warrant further investigation. Diverticulitis should be considered, in addition to IBD, when patients with SpA present with lower gastrointestinal symptoms. Disclosure of Interest: None declared